Predicitve Value of FDG Uptake in the Remaining Adrenal Gland Following Adrenalectomy for Adrenocortical Cancer - Loewe, Ruben; Rogowski-Lehmann, Natalie; Pfluger, Thomas; Reincke, Martin; Hahner, Stefanie; Bluemel, Christina; Fassnacht, Martin; Beuschlein, Felix (Hormone and Metabolic Research, 2020)
Following initial surgery, patients with adrenocortical carcinoma (ACC) are commonly treated with the adrenolytic substance mitotane in an adjuvant or therapeutic setting. Treatment responses, however, are variable. The objective of the study was to investigate a possible correlation between FDG-PET activity of the remaining adrenal gland and therapeutic response of mitotane treatment. This is a retrospective study enrolling patients from two German centers with operated ACC and minimal information on PET-CT scanning. Eighty-two ACC patients after adrenalectomy were included (66 treated with mitotane and 16 without medical therapy). FDG uptake of the contralateral adrenal gland, liver and mediastinum was analyzed from a total of 291 PET/CT scans (median 4 scans per patient) and correlated with clinical annotations including overall and recurrence free survival. The majority of patients (81%) displayed a temporary increase in adrenal FDG uptake within the first 18 months following surgery, which was not associated with a morphological correlate for potential malignancy. This increase was mainly present in patients treated with mitotane (51/61, 84%) but less frequent in the control group (4/7, 57%). No direct correlation with mitotane plasma levels were evident. Patients following R0 resection with high adrenal uptake showed a tendency towards better clinical outcome without reaching a significance value (HR 1.41; CI 0.42–4.75; p=0.059). FDG update of the contralateral adrenal gland may not be misinterpreted as sign of malignancy but might be rather associated with a trend towards better clinical outcome.
Keywords: adrenocortical cancer; FDG-PET; prognostic value; mitotane